Latency time and changes in the ejaculate of rams in warm humid climates - Muñiz-Castillo, Jorge Alejandro; Cruz-Zavala, Daniel; Sosa-Pérez, Gustavo; Flores-Santiago, Ever del Jesús; Hernández-Marín , José Antonio; Cadena-Villegas , Said (Ecosistemas y Recursos Agropecuarios, 2025)
The study’s objective was to quantify the changes in the ejaculate characteristics of rams over three successive mounts, as well as the latency time between mounts. Eight crossbred rams of Pelibuey and Black Belly were used, which were divided into two groups. The group of young rams under 12 months old with an initial live weight of 41.6 ± 3.25 kg, and the group of mature rams, between 24 and 36 months old, and initial live weight of 54.3 ± 8.73 kilograms. The evaluated variables included ejaculate volume, mass motility, scrotal circumference, percentage of live spermatozoa, reaction time to the first mount, and latency time. Mature rams showed differences in seminal characteristics between groups and consecutive events (P < 0.05). On extraction days, there were no differences (P > 0.05) in volume and percentage of live spermatozoa between groups. Mature rams showed shorter latency times with differences between groups and consecutive events (P < 0.05). On different ejaculate extraction days, mature rams maintained consistent latency times. Sexually mature rams exhibited higher reproductive efficiency compared to young rams. Ram age is a factor that influences seminal characteristics and sexual behavior.